Chapter 9 Fyodor Dostoevsky and the Ungrateful Biped - Farrell, John (Taylor & Francis, 2023)
Dostoevsky's Notes from Underground offers the most profound and conflicted treatment of the utopian dilemma. Utopian planning, symbolized by the Crystal Palace in London built for the Great Exhibition of 1851, threatens the narrator's vanity and sense of freedom, yet he cannot conceal from himself the irrational and shameful basis of his resistance to the happiness it represents.